Chicago Paper - Geographic Distribution of Sulfur in West Virginia Coal Beds (with Discussion) - I. C. White (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1920)
Only two factors appear to be directly responsible for the geographic distribution of sulfur in the coal fields of West Virginia: these are the stratigraphic position of the coals in question, and the eastward or westward location of the deposits. There appears to be a progressive increase in the sulfur content of West Virginia coals from the oldest Peqnsylvanian deposits in the Pocahontas, New River, and Kanawha Groups of the Pottsville Series up through the Allegheny, Conemaugh, and